THE PAST AND PRESENT OF THE TRANSYLVANIAN SALT WATERS - CZELLECZ, Boglárka; SZOPOS, Noémi-Mária (Studia Universitatis Babeș-Bolyai Geographia, 2018)
The Transylvanian salt was always in the center of attention from different points of view during different periods. In the past centuries, identifying the location and extent of this resource was the most important issue, since mining and trading were top priority activities. In recent times the formation of the salt deposits is mostly in the attention of the scientists, so salt is a subject of a continuous interest. Waters that get their mineralization by interacting with the salt beds have been less researched. They were in the center of attention mostly in the second part of the 19th century, while in the recent times just a few studies have dealt with this topic. Field observations carried out in 2016 revealed that the number of salt water occurrences at surface decreased over time. By exploring the causes why these sources have disappeared, we succeeded to gather valuable information about the appreciation of the salt waters during the centuries. Until the 14th century all salt products were considered as part of the land, while in the late Middle Ages this perception was replaced with the practice of regalia, the exclusive right of the king over all the salt resources, including the salt waters. The rights that the regalia empowered the kings were not equally applied over time. The most rigurous actions to protect the rights over this resource were applied during the 19th century. This study presents the legal background and regulation of usage of the salt waters in Transylvania from the Middle Ages until the 20th century. A case study is also presented in order to illustrate the rate of disappearance and present situation of the salt sites in the area South of Cluj-Napoca city.